Signal Processing Techniques for Diagnosis Rotor Faults in Small Wind Turbine Motor - Resen, Ali K.; Mahmood, Faleh H.; Kadhim, Hussein T. (Iraqi Journal of Science, 2018)
The core objective of this paper was to diagnosis and detect the expected rotor faults in small wind turbine SWT utilize signal processing technique. This aim was achieved by acquired and analyzed the current signal of SWT motor and employed the motor current signature analysis MCSA to detect the sudden changes can have occurred during SWT operation. LabVIEW program as a virtual instrument and (NI USB 6259) DAQ were take advantage of current measurement and data processing.